PENGGUNAAN MEDIA DI LINGKUNGAN APARATUR PEMERINTAH - Rustam, H. Muhammad (Jurnal Insani, 2014)
These studies focus on the symptoms in the use of the communication medium among government agencies. Focus based on the development of convergence media. With the method of measurement, the results showed that in the middle of the situation continues the development of media convergence at this time, the respondent was seen still uses conventional media such as magazines/tabloids, newspapers and television as a means to communicate. In addition, they still look to up date themselves to the development of new media/ convergence. Updateing themselves, proved that they have a range of comunication channels (channel) available in internet such as an e-mail accounts and others.